2006
DOI: 10.1109/map.2006.277130
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Sensor Motes for Small Satellite Applications

Abstract: Motes are low-cost COTS (commercial off-the-shelf) microchips, which integrate a processor, onboard sensor, RF communications link, and a power unit. High levels of power efficiency can be achieved with the use of the IEEE 802.15.4 protocol for communication between the motes, allowing long-term periods of operation for motes and reducing the power requirements of a spacecraft. The article examines the feasibility of using sensors for harness reduction between satellite subsystems, and for inter-satellite netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In [154], the authors suggest the use of "motes" for WSN applications on mini, micro and nano satellites. Motes are wireless microsensors that integrate a low-power micro-controller, a RF transceiver, and a power supply with one or more sensors attached or embedded.…”
Section: Some Applications In the Aerospace Fieldmentioning
confidence: 99%
“…In [154], the authors suggest the use of "motes" for WSN applications on mini, micro and nano satellites. Motes are wireless microsensors that integrate a low-power micro-controller, a RF transceiver, and a power supply with one or more sensors attached or embedded.…”
Section: Some Applications In the Aerospace Fieldmentioning
confidence: 99%
“…The study reported viable technology for implementing an intra-car wireless sensor network. Two related studies reported that the wireless harness with IEEE 802.15.4 or ZigBee reduced the power requirements [23] and the satellites' power consumption [24]. The related study [25], [27], [28] for the 3U CubeSat also attempted to construct the wireless harness called SKITH (SKIpTheHarness) of the InnoCube project.…”
Section: Related Work On Satellite Design For Cubesatsmentioning
confidence: 99%
“…At present, aircraft, vehicles, industrial machinery and other equipment mainly transmit data through cable, but the weight, volume, cost, reliability and other problems brought by the huge cable network restrict the carrying capacity, development cycle and maintainability of the equipment [1]. For the closed metal space with complex, compact and narrow layout, the traditional radio frequency and optical wireless communication technology will experience strong fading and dense multipath effect, which makes the signal unable to transmit reliably.…”
Section: Introductionmentioning
confidence: 99%